Probabilities for time-dependent properties in classical and quantum mechanics - Losada, Marcelo Adrián (2013)
We present a formalism which allows one to define probabilities for expressions that involve properties at different times for classical and quantum systems and we study its lattice structure. The formalism is based on the notion of time translation of properties. In the quantum case, the properties involved should satisfy compatibility conditions in order to obtain well-defined probabilities. The formalism is applied to describe the double-slit experiment.